Gender representation in Iran’s national television and the significance of critical media literacy for Iranian women - Kachalami, Kobra Mohammadpour; Lee, Yok Fee (Centre for Promoting Knowledge, 2018)
Media culture plays a significant role in constructing gender identity, femininity and masculinity. Since the Iranian national TV tries to perpetuate gender oppression by oppressive representation of gender, this paper intends to discuss the importance of critical media literacy for Iranian women to perceive oppressive gender representation and to struggle against gender discrimination in Iran. From earlier academic discussions on gender representation in Iranian national TV series and advertisements, it has been identified that gender is portrayed based on patriarchal values and belief. The studies also indicate how the Iranian dominant group uses media such as television as an ideological tool to legitimize and naturalize sexist ideology. By focusing on a critique of sexist ideology and politics of gender representation, critical media literacy could empower Iranian women to understand the oppressive role of Iran’s national television productions in perpetuating male domination and to struggle against the dominant sexist ideology.